2022
DOI: 10.1016/j.procs.2021.12.306
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Nature of Social Media Content Propagating COVID-19 Vaccine Hesitancy: Ukrainian Case

Abstract: COVID-19 became an issue affecting different parts of our life. Different communication campaigns use vaccination as an information peg, argument in discussions, and so on. As a result, they have an impact on people’s attitudes to immunization. We applied the message analysis to the dataset of social media posts from Ukraine to detect the messages used in the communication regarding the vaccine and reveal communication campaigns propagating these messages. We found five campaigns launched by different actors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Vaccine hesitancy, however, refers to emotional resistance to adopting vaccines, which cannot be explained using the rational constructs included in the HBM ( Larson et al, 2022 ). Furthermore, multiple social media content with ulterior political motives often propagate vaccine hesitancy ( Zakharchenko et al, 2022 ). Thus, developing and including an updated and expanded scale on vaccine hesitancy in survey instruments is crucial to capturing the irrational and multidimensional nature of vaccine hesitancy and to expanding HBM into the realm of emotional decision-making .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccine hesitancy, however, refers to emotional resistance to adopting vaccines, which cannot be explained using the rational constructs included in the HBM ( Larson et al, 2022 ). Furthermore, multiple social media content with ulterior political motives often propagate vaccine hesitancy ( Zakharchenko et al, 2022 ). Thus, developing and including an updated and expanded scale on vaccine hesitancy in survey instruments is crucial to capturing the irrational and multidimensional nature of vaccine hesitancy and to expanding HBM into the realm of emotional decision-making .…”
Section: Discussionmentioning
confidence: 99%
“…By demonstrating lower success rates of prior interventions, we clearly showed the resilience of vaccine hesitancy, corroborating Larson et al’s (2022) argument. Larson et al (2022) have challenged the prevailing unidimensional views about vaccine hesitancy, equating it with misjudgment or a flawed decision, and instead have argued that vaccine hesitancy is a firm belief cultivated and reinforced by diverse factors (such as politics, religion, culture, and lifestyle) in our society ( Zakharchenko et al, 2022 ). Additionally, our results showing how a small number of interventions succeeded, in comparison to a large number of failed campaigns, provide insight into designing an efficacious intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that HCWs were overburdened, hence the burnout and demotivation phenomenon, reflecting the current tenor in the literature [52–54], but evidence of retention strategies, incentives, and other professional support is so far limited. Our findings also highlighted how social media altered communication and stoked widespread anxieties that permeated other contexts [55–57]. Fear‐based narratives are a common source of misinformation on social media, which has increased apathy and low public engagement [18, 58].…”
Section: Discussionmentioning
confidence: 87%
“…Due to the AI-generated nature of virtual influencers' content, it may not be based on genuine opinions or experiences, which makes it difficult to determine the integrity and accountability of communication. It may even lead to psychological problems such as gender stereotypes (Zakharchenko et al, 2020) and body image concerns .…”
Section: Front-end Ai and Back-end Aimentioning
confidence: 99%